2021
DOI: 10.1002/mma.7317
|View full text |Cite
|
Sign up to set email alerts
|

Analytical manner for abundant stochastic wave solutions of extended KdV equation with conformable differential operators

Abstract: This work investigates the Wick‐type stochastic and extended Korteweg‐de Vries (EKdV) equation under conformable differential operators. Novel wave solutions with soliton and periodic types are produced to the deterministic EKdV under conformable differential operators. Abundant stochastic wave solutions are explored for the Wick‐type stochastic EKdV equation by using conformable differential operators and the inverse Hermite transform. The stochastic soliton and periodic solutions are denoted as functional so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
(107 reference statements)
0
5
0
Order By: Relevance
“…The noise arising in physics, telecommunication networks, hydrology, medicine, and so on can be modeled by stochastic partial differential equations. One of the important research directions of stochastic partial differential equations is the stochastic wave, which has been studied by many authors (see [1][2][3]). Optical solitons are used to transmit very large amounts of data at the speed of light without error and loss over very long distances (see .…”
Section: Introductionmentioning
confidence: 99%
“…The noise arising in physics, telecommunication networks, hydrology, medicine, and so on can be modeled by stochastic partial differential equations. One of the important research directions of stochastic partial differential equations is the stochastic wave, which has been studied by many authors (see [1][2][3]). Optical solitons are used to transmit very large amounts of data at the speed of light without error and loss over very long distances (see .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have employed stochastic nonlinear Schrödinger equations to describe the behavior of stochastic optical solitons in nonlinear media. These equations have been extensively discussed in literature, with references such as [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many authors have found an interest in nonlinear models for stochastic systems of differential equations [26][27][28][29][30], which have numerous applications. They also found both analytical and numerical solutions to their system using various methodologies.…”
Section: Introductionmentioning
confidence: 99%